Troponin T parallels structural nerve damage in type 2 diabetes: a cross-sectional study using magnetic resonance neurography - Jende, Johann; Gröner, Jan; Kender, Zoltán; Hahn, Artur; Morgenstern, Jakob; Heiland, Sabine; Nawroth, Peter Paul; Bendszus, Martin; Kopf, Stefan; Kurz, Felix T. (Diabetes, 2020)
Clinical studies have suggested that changes in peripheral nerve microcirculation may contribute to nerve damage in diabetic polyneuropathy (DN). High-sensitivity troponin T (hsTNT) assays have been recently shown to provide predictive values for both cardiac and peripheral microangiopathy in type 2 diabetes (T2D). This study investigated the association of sciatic nerve structural damage in 3 Tesla (3T) magnetic resonance neurography (MRN) with hsTNT and N-terminal pro-brain natriuretic peptide serum levels in patients with T2D. MRN at 3T was performed in 51 patients with T2D (23 without DN, 28 with DN) and 10 control subjects without diabetes. The sciatic nerve’s fractional anisotropy (FA), a marker of structural nerve integrity, was correlated with clinical, electrophysiological, and serological data. In patients with T2D, hsTNT showed a negative correlation with the sciatic nerve’s FA (r = −0.52, P < 0.001), with a closer correlation in DN patients (r = −0.66, P < 0.001). hsTNT further correlated positively with the neuropathy disability score (r = 0.39, P = 0.005). Negative correlations were found with sural nerve conduction velocities (NCVs) (r = −0.65, P < 0.001) and tibial NCVs (r = −0.44, P = 0.002) and amplitudes (r = −0.53, P < 0.001). This study is the first to show that hsTNT is a potential indicator for structural nerve damage in T2D. Our results indirectly support the hypothesis that microangiopathy contributes to structural nerve damage in T2D.
Gesehen am 28.05.2020